RELAY ZONES BETWEEN MESOSCOPIC THRUST FAULTS IN LAYERED SEDIMENTARY SEQUENCES - Nicol A.; Gillespie P.A.; Childs C.; Walsh J.J. (My University, 2002)
We examine the geometry, formation and destruction of relay zones in well-bedded sedimentary sequences containing thrust fault segments with maximum observed displacements of 0.64-8m. Contractional, extensional and neutral relay zones are distinguished based on the stepping sense of the interacting fault segments and the orientation of the associated fault slip vectors. Large displacement gradients (0.17-1.0) in relay zones are mainly accommodated by folding with aggregate displacements maintained across segment boundaries and a significant component of the fault slip converted to fold-related shortening.Folds in contractional relay zones verge in the direction of hanging wall motion, with the steeper limb defining a parallelogram-shaped zone between thrusts. Fault segment lengths are established after minimal displacement and folds in relay zones grow between segments as displacement accrues on the thrusts. With increasing displacement, upper and lower thrust tip lines in contractional and extensional relay zones are fixed at stratigraphic boundaries while the lateral thrust tip lines may propagate in a strike-parallel direction. Upper and lower tip lines may eventually propagate to bypass relay zones that formed early in the fault growth history. Contractional relay zones remain intact at higher displacements than extensional relay zones.
Keywords: RELAY ZONES; MESOSCOPIC THRUST FAULTS; LAYERED SEDIMENTARY SEQUENCES